ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB): BASED ON EMPLOYEE COMPETENCE AND ITS EFFECT ON EMPLOYEE PERFORMANCE - Suswati, Endang (Universitas Brawijaya, Indonesia, 2022)
This study investigates the factors that influence employee performance at a dairy cow company in Batu City, Indonesia. This study uses employee competence variables that affect employee performance with organizational citizenship behavior (OCB) as a mediating variable. This research is categorized as an explanatory research type. Respondents in this study were all employees. The determination of the number of samples in this study used the saturated sample technique with a total sample of 100 respondents. The data collection method used a questionnaire. The data was analyzed using Smart Partial Least Square (SmartPLS). The analysis results prove that employee competence significantly affects organizational citizenship behavior (OCB). Employee competence has a significant effect on employee performance. Organizational Citizenship Behavior has a significant effect on Employee performance. Competency significantly affects employee performance through Organizational Citizenship Behavior (OCB). The next researcher can re-examine and develop the concepts used for research and contribute to the renewal and development of human resource management science by integrating other variables such as organizational commitment, job satisfaction, and leadership.